Shedding social media: Dewey and the changing needs of education for democratic engagement - Beth Cross (University of Aberdeen, School of Education, 2017)
This paper focuses on Dewey's rejoinder to the classic text which occasioned the conference on Democracy and Education. Dewey wrote Freedom and Culture with the hindsight provided by world wars and the rise of totalitarian states. In this work, he focusses on the learning for democracy that happens in people's everyday lives and on the dynamics that thwart and deliberately deform civic life. In particular, he is concerned about the impact of media on democratic judgement. Dewey argues that media manipulation of public opinion can put "hate in place of attempts at understanding". In this article I look at Dewey's analysis of the problem and his proposed line of redress in light of more recent scholarship. This provides the lens for analysing recent political engagement in the UK that is relevant to dynamics across the Global North. I argue that social media has intensified the dynamics which concerned Dewey and at the same time have changed the rules of engagement and the kinds of critical media literacy required. If democracy is the art of associative living, it requires not only scientific inquiry but relational skills, grounded in opportunities for concrete experimentation such as those provided by the shed movement.